2015
DOI: 10.1039/c5tc01410g
|View full text |Cite
|
Sign up to set email alerts
|

Spatially inhomogeneous, stepwise phase transitions in a thiazyl diradical: a structural mismatch induced by lattice transformation

Abstract: A heterocyclic thiazyl diradical, bis(1,2,3,5-dithiadiazolyl)-4,4 0 -biphenylene (1), was synthesized, and its structural and thermodynamic properties were characterized. This compound exhibits unique spatially inhomogeneous, first-order phase transitions at 306 and 359 K, in a stepwise fashion. The unit cell in the high-temperature phase above 359 K consists of four regular p-stacking columns with the same stacking manners having a uniform interplanar distance d. These four columns are connected by intermolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…56,63 Such reversible phase transitions between different polymorphs in DTDA chemistry are extremely rare. 57,59,60,64 The observation of two single-crystal-to-single-crystal transitions between paramagnetic phases associated with 3β ↔3γ ↔ 3δ is almost unprecedented in DTDA chemistry. The successive breakdown in pancake bonding interactions in Preuss' Ln(hfac)3(boaDTDA)2 complex, perhaps provides the closest comparison (also two transitions) but a much more pronounced change in magnetic response since the latter is based around cleavage of the enthalpically favorable π * −π * pancake bond, switching from an S = 0 state to two S = ½ spins.…”
Section: Discussionmentioning
confidence: 99%
“…56,63 Such reversible phase transitions between different polymorphs in DTDA chemistry are extremely rare. 57,59,60,64 The observation of two single-crystal-to-single-crystal transitions between paramagnetic phases associated with 3β ↔3γ ↔ 3δ is almost unprecedented in DTDA chemistry. The successive breakdown in pancake bonding interactions in Preuss' Ln(hfac)3(boaDTDA)2 complex, perhaps provides the closest comparison (also two transitions) but a much more pronounced change in magnetic response since the latter is based around cleavage of the enthalpically favorable π * −π * pancake bond, switching from an S = 0 state to two S = ½ spins.…”
Section: Discussionmentioning
confidence: 99%
“…However,i nh ysteretic spin-switch systems, the LT !HT transition takes place at ad ifferent temperature than that of the HT!LT transition. [23,24] Among the group of bistable DTAr adicals, the case of 1,3,5-trithia-2,4,6-triazapentalenyl (TTTA) is especially remarkable, since its bistability region spans 70 degrees and encompassesr oom temperature (T c› = 310 K, T cfl = 230 K) [7,[25][26][27][28][29][30][31][32][33][34][35] (Figure 1a). Bistable materials based on transition-metal complexes have been associated with spin transitions for many years [3][4][5] ,b ut recent work has demonstrated that purely-organic radicals can also be versatile building blocks to achievebistability.…”
Section: Introductionmentioning
confidence: 99%
“…Among the purely organic radicals exhibiting spin‐switch behavior, the family of dithiazolyl (DTA) neutral radicals is particularly interesting, as it has furnished numerous switchable materials, some of them presenting hysteretic phase transitions, and some of them presenting non‐hysteretic phase transitions . It is worth mentioning that the closely related family of dithiadiazolyl radicals has most recently furnished two examples of non‐hysteretic spin transition compounds . Among the group of bistable DTA radicals, the case of 1,3,5‐trithia‐2,4,6‐triazapentalenyl (TTTA) is especially remarkable, since its bistability region spans 70 degrees and encompasses room temperature ( T c↑ =310 K, T c↓ =230 K) (Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this plausibility criterion applies to all the suspected ill-refined structures analyzed in this work and deposited as files SM3a to SM3h in the supporting information, viz. (3a) CSD refcode ADUVEA (Usuda et al, 2002), (3b) BEYVEH01 (Akkurt et al, 2007), (3c) CUNBET (Popsavin et al, 2009), (3d) LOPLEJ (Long et al, 2014), (3e) CUQCAU02 (Suizu et al, 2015), (3f) SAGDUA (Yamada et al, 2004), (3g) AHEDAU (Naik et al, 2015) and (3h) MEWMUY (Praveen et al, 2013).…”
Section: Figure 15mentioning
confidence: 99%